E-COMMERCE BUMBU MASAKAN KELOMPOK TANI KWT ( KELOMPOK WANITA TANI ) SETIA DESA PAKKODI KAB. ENREKANG - Wahyuddin, Wahyuddin; Alam, Syahirun; Rosadi Said, Imran (Jurnal Sintaks Logika, 2021)
Advances in technology that are increasingly rapidly cannot be separated from human intervention creating sophisticated inventions. That's what makes humans can not be separated from technology, even in everyday life. Technological advances have penetrated various fields including the economic field. The internet economy encourages globalization and networking in the business world. The purpose of this research is to create an application program that can be used to make it easier to promote and sell seasoning products for loyal kwt farmer groups (women farmer groups). The research method used is a survey research method used to collect data or information about a large population using a relatively small sample and application testing using black box and white box methods, the test results are stated that the test has been successful and is free from logical function errors. This application is made using html code, javascript, php, css, and framework with My SQL database on XAMPP. The result of this research is the creation of a web-based e-commerce application so that it can facilitate the transaction process and provide broad information.